Are they being heard? An insight into the lived experience of Hyperphenylalaninaemia - Amy, Goulding (2010)
Introduction: This dissertation is a qualitative research study examining adult female patients experience of living with Hyperphenylalaninaemia (HPA) with a focus on their adolescence. This chapter aims to introduce the chosen research phenomenon, rationalising this topic choice through the utilisation of background literature pertaining to the specific subject area. This chapter will conclude with table 1, a brief outline of the study structure. HPA: HPA is a mild variant of the autosomal, recessive, metabolic disease Phenylketonuria (PKU). HPA is classified by persistent but mildly raised serum phenylalanine levels of up to 600µM/L. People with mild PKU have phenylalanine levels between 600-1200µM/L. The levels of classic PKU are 1200µM/L or more (Weglage et al 2001). People with HPA have difficulty metabolising the amino acid phenylalanine (Warrel et al 2005) due to a deficiency of the enzyme phenylalanine hydroxylase (Bosh et al 2007). High phenylalanine concentrations can be associated with impaired brain growth and fewer nerve cells. Rationale for choice of study: In the early 1970’s it was enough to know that dietary treatment could reduce global developmental delay in classic PKU (Griffiths 2000). Adults with the disorder often had severe learning difficulties because of poor metabolic control. Gaining consent to question patients proved ethically difficult. Thus adults with the condition were not studied and much of the research carried out regarded children, whose outcomes improved as knowledge advanced. Now however the question is whether treatment can fully normalise intellectual development (Griffiths 2000). Patients with good metabolic control are reaching adulthood and although currently there is limited literature concerning the reality of having PKU in adulthood, this situation is improving as more research is published. There is a wealth of research on the intellectual, neurocognitive and psychosocial state of children with PKU (Simons et al 2008; Smith and Knowles 2000; Sullivan and Chang 1999) and there is substantial knowledge debating the outcome of children with classic PKU who have been treated with a strict low-phenylalanine diet and those who have not (Channon et al 2007; Gassio et al 2005; Griffiths 2000). However, there is little research on HPA and potential impairment. Literature regarding adult patients who have low yet elevated phenylalanine levels and are not on treatment is virtually nonexistent. (Gassio et al 2005) The majority of the empirical research carried out regarding patients with PKU and HPA utilises parents, teachers, or professionals opinions (Stemedink et al 2000; Ladolt et al 2002, Weglage et al 2000). Asking patients’ about their experiences, rather than asking third parties could bring about an innovative approach to gathering literature on HPA (Landolt et al 2002). Much of the methodology of existing literature on HPA is very technical and condition orientated or is not coterminous due to the use of various test batteries. This has often resulted in reduced objectivity or reliability (Spronsen and Burgard 2008; Burgard 2000). It is thought that patient focused research might highlight the future validity of humanistic, nursing-led literature in tandem with scientific, medical literature. Therefore a study which asks patients how they feel, adopting humanistic principals to gathering and analysing data would be unique and could be invaluable to providing tailor made services for future generations